Formação continuada de professores: contribuições da EAPE (Escola de Aperfeiçoamento dos Profissionais de Educação) no desenvolvimento profissional docente - Lacerda, Vera Lúcia (2016)
This study aims to analyze the contributions of the School of Education Professionals Enhancement - EAPE for the professional development of teachers. Conceptions built by the participating teachers in training activities promoted by EAPE, which in turn are steeped in a culture that will outline the identity of the professional who wants to form influence the professional development. The research was guided by the following questions: What are the contributions of continuing education activities for teachers, promoted by EAPE for the professional development of teachers? As the training practices by teachers are understood? As the process of construction of teaching knowledge and professional identity from the continuing education? What changes occur in the pedagogical practice conceptions of the teachers participating in the training activities? The research, qualitative approach, had as its starting point the analysis of the literature of the area, having been grounded primarily by the following authors: Dubar (1997); Pepper (2000); Melo (2007); Nóvoa (2008); Gatti (2009); Marcelo García (2009); Imbernon (2010); Marcelo García and Vaillant (2012); Tardif (2014). Data were collected through questionnaires and focus group which participated teachers of two schools of the Federal District. From the following considerations of data content analysis are presented: the continuing education promoted by EAPE is seen as fertile ground for the development and redesign of teaching knowledge, for the establishment of professional identity, to reflect the pedagogical practices and therefore for the professional development provided it is planned and carried out according to the specific demands of each situation and with the direct involvement of the teachers. Designing teaching experiences as a starting point for the construction of new knowledge, while in constant flux and sedimentation, allows reframing the preparation processes. The school is one of the privileged spaces for training, construction of professional identity and teaching knowledge, to be associated with the individual and collective experiences, related to the professional development of teachers.